Sistema de control atencional y rendimiento académico en estudiantes de psicología de tercer y octavo semestre de una universidad de Cartagena (2015)
In this research the operation of attentional control with academic performance, 60 psychology students, third and eighth semester relate. To do this, makeit a psychological tests, Porteus maze, Stroop test and trail making test, like a neuropsychological evaluation tool, with a nonexperimental design, correlational cross-sectional design. From the results, a relationship between attentional control system and academic performance is presumed.